2009
DOI: 10.1002/jemt.20703
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian sperm quality and aromatase expression

Abstract: In most mammalian species the aromatase is encoded by a single gene (cyp19), which contains 18 exons, 9 of them being translated. In adult rats, together with Leydig cells germ cells represent an additional source of estrogens. The amount of P450arom transcript is threefold higher in pachytene spermatocytes compared to younger cells (spermatogonia-preleptotene spermatocyte) or round spermatids; conversely, aromatase activity is more intense in haploid cells. In man besides Leydig cells, we have shown the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 67 publications
1
29
0
1
Order By: Relevance
“…P450arom is the member of the cytochrome P450 gene superfamily, and is a product of transcription of a single copy of the Cyp19 gene. In humans, this is located on chromosome 15 [13][14][15], in rats on chromosome 8, and in mice on chromosome 9 [16]. The enzyme is a microsomal complex composed of two proteins: specific heme-glycoprotein cytochrome P450 aromatase, which contains a steroid binding pocket, and ubiquitous NADPH-cytochrome P450 reductase [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…P450arom is the member of the cytochrome P450 gene superfamily, and is a product of transcription of a single copy of the Cyp19 gene. In humans, this is located on chromosome 15 [13][14][15], in rats on chromosome 8, and in mice on chromosome 9 [16]. The enzyme is a microsomal complex composed of two proteins: specific heme-glycoprotein cytochrome P450 aromatase, which contains a steroid binding pocket, and ubiquitous NADPH-cytochrome P450 reductase [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, this is located on chromosome 15 [13][14][15], in rats on chromosome 8, and in mice on chromosome 9 [16]. The enzyme is a microsomal complex composed of two proteins: specific heme-glycoprotein cytochrome P450 aromatase, which contains a steroid binding pocket, and ubiquitous NADPH-cytochrome P450 reductase [13,14]. It is known that aromatase is widely distributed in the testes of mammals, including humans [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is reported that the low in FSH, testoterone and estrogen level can cause sperm immaturity. [22][23][24] Immature spermatozoa is a source of ROS and lack of antiapoptotic factor Bcl-xl. 13 …”
Section: Discussionmentioning
confidence: 99%